Photovoltaic Electrochemically Driven Degradation of Calcon Dye with Simultaneous Green Hydrogen Production - Câmara Cardozo, Jussara (2022)
In this study, for the first time, the production of green hydrogen gas (H2) in the cathodic compartment, in concomitance with the electrochemical oxidation (EO) of an aqueous solution containing Calcon dye at the anodic compartment, was studied in a PEM-type electrochemical cell driven by a photovoltaic (PV) energy source. EO of Calcon was carried out on a Nb/BDD anode at different current densities (7.5, 15 and 30 mA cm−2), while a stainless steel (SS) cathode was used for green H2 production. The results of the analysis by UV-vis spectroscopy and total organic carbon (TOC) clearly showed that the electrochemical oxidation (EO) of the Calcon dye after 180 min of electrolysis time by applying 30 mA cm−2 reached up to 90% of degradation and 57% of TOC removal. Meanwhile, under these experimental conditions, a green H2 production greater than 0.9 L was achieved, with a Faradaic efficiency of 98%. The hybrid electrolysis strategy is particularly attractive in the context of a circular economy, as these can be coupled with the use of more complex water matrices to transform organic depollution into an energy resource to produce H2 as a chemical energy carrier.